(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Hepatitis B virus (HBV) infection can lead to a chronic state of infection, and cytokines play a critical role in viral infections. Interleukin 17 (IL-17) has a role in many chronic inflammatory diseases like pulmonary infection, psoriasis, inflammatory bowel disease, and rheumatoid arthritis, and many studies confirmed that the IL-17 associated with a progressive inflammation during infection by lymphocytic choriomeningitis virus. Therefore, IL-17 may play a role during HBV infection. Objective: To compare the serum level of IL17 in patients with chronic HBV infection to those in control group, additionally, to assess the correlate IL-17 in the patient groups with viral load, liver enzyme levels, such as alkaline phosphatase (ALP), aspartate transaminase (AST), alanine transaminase (ALT), total serum bilirubin (TSB). Methods: In a case–control study, IL-17 (ELISA) kits, viral load by real-time polymerase chain reaction, and liver enzymes kits from Randox and Bio Merieux were measured in the 70 untreated chronic HBV patients gathered from Baghdad Medical City’s Hepatology and Gastroenterology Teaching Hospital compared with eighteen volunteers as control group in winter of 2023. Results: IL-17 significantly increased in chronic HBV patients (75.35±33.58 pg/ml) than in the control group (58.23±10.33 pg/ml) (p-value 0.036). Serum IL-17 levels showed no correlation with ALT, AST, ALP, TSB, or viral load. Conclusion: Patients with chronic HBV had elevated serum levels of IL-17, a sign of ongoing immune activity. Moreover, there was no discernible relationship between IL-17 with liver enzymes and viral load. Keywords: HBV, IL-17, ALT, AST Citation: Al-Jizani ASN, Al-Ubaidi AEM, Khassaf SA, Al-Jaryan EAJ. Investigating the potential of IL-17 in chronic HBV Infection. Iraqi JMS. 2024; 22(1): 164-169. doi: 10.22578/IJMS.22.1.18